TYPES OF DEIXIS IN SONG LYRICS SNOWMAN BY SIA - Meriska Yosiana (Asosiasi Dosen Muda Indonesia, 2023)
Deixis is words or phrases that are used as reference to something related to the speaker. There are three types of deixis, namely personal deixis, temporal deixis, and spatial deixis. This study aims to find out types of Deixis and the dominant deixis used in Song Lyrics Snowman by Sia. Sia is an is an Australian singer and songwriter who has unique characteristics. The method used descriptive qualitative because the data are in the form of words and phrases. The source of the data was taken from Sia’s song entitled Snowman. After analyzing the data, the results of study showed that 65 words of deixis. 40 or 65.5% personal deixis, 15 or 23% spatial deixis, 10 or 15.5% temporal deixis in Sia's song lyrics Snowman. There are person deixis words used such as I, me, my, you, your, we, and Mrs. Snow. While in spatial deixis, there are some deixis words used such as this, that, where, below, home, in North pole, and From. Temporal deixis used in this song are now, forever, all seasons, till, and Christmas